PERAN KOMUNIKASI PEMASARAN TERPADU TERHADAP UMKM DALAM MENJAGA EKSISTENSI SAAT PANDEMIC COVID-19 - Oktri Permata Lani; Nil Firdaus (Tamwil, 2022)
In the current reality, the decline in the value of income related to the UMKM sector, especially in food, has a negative impact. This can happen related to economic conditions, regulations issued by the government such as PSBB, or other terms PPKM. Of course, this can make people more selective in buying food outside the home. This phenomenon indirectly interferes with the sustainability of UMKM in the food sector, due to the tendency of prospective consumers to be more selective in order. Of course, business owners are encouraged to maintain their business, especially midwives, by looking at new possibilities and business models, instilling a "New Normal" method for sustainability, and maintaining the existence of their business. The purpose of this study is to look at the role of integrated marketing communications for UMKM in maintaining its existence during the COVID-19 pandemic. Using the Literature Review method.